Diversification of accommodation offers depending on critical economies of scale for travel business - Tomas Macak; Jan Hron; Monika Jadrna (Cogent Business & Management, 2020)
The world's oldest travel company Thomas Cook, the British tour operator with 19 million yearly clients, after 178 years of service, has officially announced that it would be liquidating its assets and filed for bankruptcy, despite attempts to rescue the brand. The low-cost travel firms and their cut-throat prices have certainly been a boon to customers, but legacy travel companies, who have been forced to decrease their prices, still not align themselves, especially if they have too diversified their activities and lost the scale advantage. In the field of today's travel business, it is not possible only to rely on case studies and best practices. But it is necessary to come up with new approaches that can deal with changes in conditions such as when confronting the tourism business risk diversification and economies of scale. This article aims to create a general identification of the tourism business management system in terms of stable (and thus, sustainable) accommodation (and accompanying services) diversification, depending on the changes in the critical quantity of economies of scale. An analytical mathematical model is used for determining the diversification and economies of scale, and the parameters are determined using a full factorial design. The results of the study verify the functionality, reliability and consistency of the designed solution using a selected enterprise case study. From a practical point of view, the solution represents re-settings of diversification of accommodation offers in terms of changing the value of the critical scale of economies and other contextual factors for business.
Keywords: 650; diversification of accommodation offers; business risk; critical scale; analytical solution; optimum of multiple variables function